2020
DOI: 10.1136/bmjmilitary-2020-001589
|View full text |Cite
|
Sign up to set email alerts
|

Concussion history is associated with increased lower-extremity injury incidence in Reserve Officers’ Training Corps cadets

Abstract: IntroductionConcussions have been associated with an increased risk of lower-extremity musculoskeletal injury (LE-MSI) in athletes and US Army soldiers, creating an added economic, physical and social burden. Yet, there is a paucity of evidence on this relationship among Reserve Officers’ Training Corps (ROTC) cadets, a group which engages in activities with high-injury risk and will subsequently commission as active duty officers. This study aimed to examine the association between concussions and LE-MSI in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The relationship between concussion and lower extremity injury has been extensively studied in the sports medicine literature, 10 , 15 , 16 with a number of hypotheses for the underlying mechanism, including resultant deficiencies in dynamic balance, neuromuscular control, cognitive accuracy, and gait performance. 4 , 14 , 27 , 31 , 40 This observation is corroborated by our study, which identified a concussion history as a significant risk factor in both the multivariate logistic regression and the machine learning models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between concussion and lower extremity injury has been extensively studied in the sports medicine literature, 10 , 15 , 16 with a number of hypotheses for the underlying mechanism, including resultant deficiencies in dynamic balance, neuromuscular control, cognitive accuracy, and gait performance. 4 , 14 , 27 , 31 , 40 This observation is corroborated by our study, which identified a concussion history as a significant risk factor in both the multivariate logistic regression and the machine learning models.…”
Section: Discussionmentioning
confidence: 99%
“…The Brier score for each algorithm was compared with the null Brier score, which is calculated by assigning each patient a probability equivalent to the population prevalence of the predicted outcome. Decision curve analysis was used to compare the benefit of implementing the best-performing algorithm to the logistic regression in practice. 16 The curve plots net benefit against the predicted probabilities of each outcome and provides the cost-benefit ratio for every value of the predicted probability. These ratios provide useful guidance for individualized decision making and account for variability in clinician and patient thresholds for what is considered high risk.…”
Section: Detailed Machine-learning Modeling Workflowmentioning
confidence: 99%
“…Furthermore, concussion history was examined as a binary (yes/no) and not a continuous variable, so conclusions on a "dosage effect" cannot be made. Consistent with previous studies, participants were asked to self-report their history of concussion but were not provided a definition (23,56,57), which may result in underreporting (58,59). The outcomes herein focused on psychological distress and QoL, so findings cannot be extended to other domains of brain health (e.g., neurocognitive and executive function).…”
Section: Discussionmentioning
confidence: 99%
“…29,47 This finding has consistently been identified in intercollegiate student-athletes, 4,7,19,20,23,26,41,43 high school and adolescent athletes, 1,42,60 community members and recreational athletes, 11,33,48 and military populations. 34,38 Likely because of diverse methods (eg, different sports, time periods, and injury definitions) and statistical/modeling approaches, important determinants remain to be elucidated, with inconsistent findings related to sex differences, 1,7,26,33 elevated MSKI rates before the concussion, 1,7,11,15,19,43,51 timing of the subsequent MSKI, 4,7,15 and subsequent MSKI mechanisms and classifications. 1,19,20,34,51 Although the underlying mechanisms contributing to higher MSKI rates have not been conclusively identified, impairments in dynamic postural control have been linked to the elevated postconcussion LEMSKI rate.…”
mentioning
confidence: 99%
“…34,38 Likely because of diverse methods (eg, different sports, time periods, and injury definitions) and statistical/modeling approaches, important determinants remain to be elucidated, with inconsistent findings related to sex differences, 1,7,26,33 elevated MSKI rates before the concussion, 1,7,11,15,19,43,51 timing of the subsequent MSKI, 4,7,15 and subsequent MSKI mechanisms and classifications. 1,19,20,34,51 Although the underlying mechanisms contributing to higher MSKI rates have not been conclusively identified, impairments in dynamic postural control have been linked to the elevated postconcussion LEMSKI rate. 27,53 It is critically important to identify and understand the MSKI risk factors that elevate individual athletes' risks above the baseline injury risk associated with sports participation.…”
mentioning
confidence: 99%